Laminate base paper and laminated paper

The laminated base paper with an anchor layer composed of ethylene-vinyl acetate copolymer resin and PHBH addresses the issue of blocking resistance, ensuring the paper remains resistant to sticking even under adverse storage conditions.

JP2025065607AActive Publication Date: 2025-04-22NIPPON PAPER IND CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023174906
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

Laminated base paper with an anchor layer on both sides tends to experience high risk of blocking during the winding process, especially when stored in high temperature and high humidity environments.

Method used

A laminated base paper is developed with an anchor layer containing an ethylene-vinyl acetate copolymer resin and PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)) on at least one surface of the paper substrate, which significantly improves the blocking resistance.

Benefits of technology

The laminated base paper exhibits excellent blocking resistance, even when wound in a roll shape and stored in high temperature and high humidity conditions, thereby preventing defects caused by blocking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065607000001_ABST
    Figure 2025065607000001_ABST
Patent Text Reader

Abstract

To provide laminate base paper with excellent blocking resistance.SOLUTION: A laminate base paper includes a paper substrate and an anchor layer. The anchor layer consists of a coating layer on at least one surface of the paper base, which contains an ethylene-vinyl acetate copolymer resin and PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate base paper and a laminate paper. [Background technology]

[0002] Paper cups have traditionally been used as liquid containers. Paper cups are made up of a body member and a bottom member, and are manufactured by first heating both ends of the body paper with hot air in a cup-forming machine, winding it around a mandrel, overlapping one end of the body paper with the other end, forming the body joint part by a heat sealing process to form a cylindrical body member, and then punching out the bottom paper while rolling it up to form the bottom member whose outer periphery stands downward (Patent Document 1).

[0003] Generally, the material used for paper cups is laminated paper, which is a base paper with a laminate layer attached by methods such as dry lamination and extrusion lamination. When manufacturing paper cups using laminated paper with a laminate layer on one side of the base paper, the base paper of the inner laminate paper is heat sealed in contact with the laminate layer of the outer laminate paper at the body bonding part, so the bonding part has a layer structure in the thickness direction from the inside to the outside in the order of laminate layer / base paper layer / laminate layer / base paper layer (Figure 2A). Even with this structure, the adhesive strength is maintained to a certain extent, but a method of further increasing the adhesive strength is to provide an anchor layer made of a thermoplastic resin on the non-laminated side of the base paper. By using this anchor layer, the order becomes laminate layer / base paper layer / anchor layer / laminate layer / base paper layer / anchor layer (Figure 2B), which can increase the adhesive strength between the base paper layer and the laminate layer. Furthermore, in order to improve the adhesive strength of this body bonded area, it is also possible to consider providing an anchor layer between the laminate layer and the base paper layer in the laminate base paper (Figure 2 (c)).

[0004] Incidentally, when manufacturing a laminate base paper having an anchor layer on such a base paper, it is necessary to first coat one surface of the base paper with an anchor layer, dry it, and wind it up as a roll, or to subsequently provide an anchor layer on the other surface in the same manner and wind it up. However, once the base paper with the anchor layer is wound up, the anchor layer provided on one surface of the laminate base paper may come into contact with the non-coated surface of the base paper that overlaps it, or with the anchor layer provided on the other surface, causing blocking. In particular, when anchor layers are provided on both sides of the base paper, there is a high risk of blocking occurring, and a solution was desired. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-214365 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a laminate base paper having excellent blocking resistance. [Means for solving the problem]

[0007] The means for solving the problems of the present invention are as follows. 1. A laminate base paper characterized by having a paper base material and, on at least one surface of the paper base material, an anchor layer which is a coating layer containing an ethylene-vinyl acetate copolymer resin and PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)). 2. The laminate base paper according to 1., wherein the weight ratio of the ethylene-vinyl acetate copolymer resin to the PHBH is 30:70 to 70:30. 3. A laminated paper characterized by having a laminate layer on the anchor layer of the laminate base paper described in 1. or 2. Effect of the Invention

[0008] The laminate base paper of the present invention has excellent blocking resistance, and even if the laminate base paper is wound into a roll and stored in a high temperature and humidity environment, blocking (sticking) is unlikely to occur, and problems caused by blocking can be prevented. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic diagram showing the evaluation of blocking properties in the examples. [Diagram 2] Schematic diagram of a cross-section of the body of a paper cup made using laminated paper having a laminate layer on one side of the base paper (a); schematic diagram of a cross-section of the body of a paper cup made using laminated paper having a laminate layer on one side of the base paper and an anchor layer on the other side (b); schematic diagram of a cross-section of the body of a paper cup made using laminated paper having a laminate layer via an anchor layer on one side of the base paper and an anchor layer on the other side (c). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Laminate base paper The laminate base paper of the present invention has a paper substrate and, on at least one surface of the paper substrate, an anchor layer which is a coating layer containing an ethylene-vinyl acetate copolymer resin and PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)). In this specification, the expression "A to B" (A and B are numerical values) means a numerical range including A and B, that is, "A or more and B or less."

[0011] (Paper base material) The paper base material is a sheet (hereinafter also referred to as "base paper") mainly made of pulp, and is obtained by making paper from a stock that further contains fillers, various auxiliaries, and the like. The pulp may be chemical pulp such as bleached hardwood kraft pulp (LBKP), bleached softwood kraft pulp (NBKP), unbleached hardwood kraft pulp (LUKP), unbleached softwood pulp (NUKP), sulfite pulp, etc., mechanical pulp such as stone grind pulp and thermomechanical pulp, wood fibers such as deinked pulp and waste paper pulp, non-wood fibers obtained from kenaf, bamboo, hemp, etc., and may be used in appropriate combinations. Among these, it is preferable to use chemical pulp of wood fiber or mechanical pulp of wood fiber, and it is more preferable to use chemical pulp, for reasons such as the fact that foreign matter is unlikely to be mixed into the paper base material, discoloration is unlikely to occur over time when recycled as waste paper raw material, the fact that it has a high whiteness and therefore provides a good surface feel during printing, and the fact that it has a high value in use, particularly when used as a packaging material. Specifically, the blending ratio of chemical pulp such as LBKP or NBKP to the total pulp is preferably 80% or more, more preferably 90% or more, even more preferably 95% or more, and particularly preferably 100%.

[0012] Examples of fillers that can be used include inorganic fillers such as talc, kaolin, calcined kaolin, clay, heavy calcium carbonate, light calcium carbonate, white carbon, zeolite, magnesium carbonate, barium carbonate, titanium dioxide, zinc oxide, silicon oxide, amorphous silica, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, barium sulfate, and calcium sulfate, and organic fillers such as urea-formalin resin, polystyrene resin, phenolic resin, and hollow microparticles. Note that fillers are not essential materials and may not be used.

[0013] Examples of various auxiliary agents include sizing agents such as rosin, alkyl ketene dimer (AKD), alkenyl succinic anhydride (ASA), polyacrylamide polymers, polyvinyl alcohol polymers, cationic starch, various modified starches, urea-formaldehyde resin, melamine-formaldehyde resin, and other dry strength agents, wet strength agents, retention agents, drainage improvers, coagulants, aluminum sulfate, bulking agents, dyes, fluorescent brighteners, pH adjusters, defoamers, UV inhibitors, anti-fading agents, pitch control agents, slime control agents, and the like, and can be selected and used as appropriate as needed.

[0014] The surface of the paper substrate may be treated with various chemicals. Examples of chemicals include oxidized starch, hydroxyethyl etherified starch, enzyme-modified starch, polyacrylamide, polyvinyl alcohol, surface sizing agents, water-resistant agents, water retention agents, thickeners, and lubricants, and these may be used alone or in combination of two or more. Furthermore, these various chemicals may be used in combination with pigments. Examples of pigments include inorganic pigments such as kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate salts, colloidal silica, and satin white, and organic pigments such as solid, hollow, and core-shell types may be used alone or in combination of two or more.

[0015] The basis weight of the paper base material can be selected appropriately depending on the desired quality and its application, but is usually 20 g / m 2 More than 600g / m 2 Less than 25 g / m is preferred. 2 More than 600g / m 2 The following is more preferred: For example, when used for packaging materials such as wrapping paper, paper bags, lids, and lining paper, the basis weight of the paper base material is 30 g / m 2 More than 150g / m 2 When used as a flexible packaging material, the paper base material preferably has a basis weight of 20 g / m 2 More than 100g / m 2 Less than 35 g / m is preferred. 2More than 80g / m 2 The following is more preferable. The soft packaging material is, among the packaging materials, particularly, a material having a density of 20 g / m 2 From 100g / m 2 It is a flexible packaging material made of thin paper of about 150 g / m2. When used for paper cups, paper containers, paper boxes, paper plates, paper trays, etc., the basis weight of the paper base material is 150 g / m2. 2 More than 300g / m 2 The following is preferred: The density of the paper base material can be appropriately selected depending on the desired qualities and ease of handling, but is usually 0.5 g / cm 3 More than 1.0g / cm 3 The following are preferred:

[0016] The method of manufacturing (papermaking) the paper base material is not particularly limited, and known manufacturing (papermaking) methods and papermaking machines can be selected, such as a Fourdrinier papermaking machine, a cylinder papermaking machine, a short wire papermaking machine, a twin-wire papermaking machine such as a gap former type or a hybrid former type (on-top former type). The pH during papermaking may be in the acidic range (acidic papermaking), pseudo-neutral range (pseudo-neutral papermaking), neutral range (neutral papermaking), or alkaline range (alkaline papermaking), and after papermaking in the acidic range, an alkaline agent may be applied to the surface of the paper layer. The paper base material may be one layer, or may be composed of two or more layers. Furthermore, when treating the surface of a paper substrate with a chemical, the method of surface treatment is not particularly limited, and known coating devices such as a rod metering size press, a pond type size press, a gate roll coater, a spray coater, a blade coater, or a curtain coater can be used.

[0017] (Anchor layer) The anchor layer is a coating layer formed by coating, and contains an ethylene-vinyl acetate copolymer resin and PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)). It is preferable that the anchor layer is a coating layer of a water-dispersed paint from the viewpoint of reducing the burden on the environment during production. Whether or not the anchor layer is a coating layer can be determined by observing the cross section with an electron microscope or the like.

[0018] Ethylene-vinyl acetate copolymer resin Ethylene-vinyl acetate copolymer resin (hereinafter also referred to as EVA) is a copolymer having ethylene and vinyl acetate as monomers, and may further have other monomers as monomers. When EVA has other monomers as monomers, the content of structural units derived from other monomers in the whole EVA is preferably 30% by mass or less. This content is not particularly limited as long as it does not impair the effects of the present invention, and can be, for example, 20% by mass or less, 10% by mass or less, 5% by mass or less, 3% by mass or less, 1% by mass or less, etc.

[0019] The glass transition temperature (Tg) of EVA is preferably -50 to 30°C. If the glass transition temperature exceeds 30°C, the adhesion to the laminate layer may decrease, resulting in insufficient interlayer adhesion. If the glass transition temperature is lower than -50°C, the EVA may become too soft and blocking may easily occur. The glass transition temperature of EVA is more preferably -40 to 20°C, and further preferably -30 to 15°C. In this specification, the glass transition temperature is the midpoint glass transition temperature measured in accordance with JIS K 7121-1987.

[0020] The molar ratio of ethylene to vinyl acetate in EVA (structural units derived from ethylene:structural units derived from vinyl acetate, also referred to as ethylene:vinyl acetate) is preferably 50:50 to 6:94. When the molar ratio of ethylene is increased, the Tg of EVA is lowered, and when the molar ratio of vinyl acetate is increased, the Tg is increased. Also, when the molar ratio of vinyl acetate is increased, the interlayer adhesion with the laminate layer tends to be increased. It is presumed that the improvement in the interlayer adhesion is derived from the polar group of vinyl acetate. When the molar ratio of ethylene to vinyl acetate is within the above range, it is easy to obtain EVA with a glass transition temperature within the above range, and it is easy to obtain a laminate base paper with excellent adhesion with the laminate layer. The molar ratio of ethylene to vinyl acetate is more preferably 45:55 to 7:93, and even more preferably 40:60 to 8:92.

[0021] ·PHBH PHBH is a copolymer of 3-hydroxybutyrate (hereinafter also referred to as 3HB) and 3-hydroxyhexanoate (hereinafter also referred to as 3HH), and is a biodegradable resin known to be produced by microorganisms. In the present invention, the PHBH used may be derived from microorganisms or petroleum resources, but it is preferable to use the PHBH derived from microorganisms in terms of reducing the environmental load.

[0022] Microorganisms that produce PHBH are not particularly limited as long as they accumulate PHBH intracellularly, but examples include bacteria of the genus Alcaligenes, such as A. lipolytica, A. eutrophus, and A. latus, as well as bacteria of the genus Pseudomonas, Bacillus, Azotobacter, Nocardia, and Aeromonas. Among them, in terms of productivity of PHBH, strains such as Aeromonas caviae, and Alcaligenes eutrophus AC32 into which genes of PHA synthase group have been introduced (Accession No. FERM BP-6038, Date of deposit on August 7, 1997, National Institute of Advanced Industrial Science and Technology, International Patent Organism Depositary, Address: Central 6, 1-1-1 Higashi, Tsukuba-shi, Ibaraki-ken, Japan) (J. Bacteriol., 179, pp. 4821-4830 (1997)) are particularly preferred. A method for obtaining PHBH from Aeromonas caviae, a microorganism of the Aeromonas genus, is disclosed, for example, in Japanese Patent Application Laid-Open No. 05-093049. These microorganisms are used by culturing them under appropriate conditions to accumulate PHBH in the cells. The carbon source and culture conditions used in the culture can be obtained according to the methods described in JP-A-05-093049, JP-A-2001-340078, etc., but are not limited thereto.

[0023] The composition ratio (mol%) of PHBH is preferably 3HB:3HH=97:3 to 75:25, more preferably 95:5 to 78:22, and even more preferably 93:7 to 80:20. If the composition of 3HH is less than 3 mol%, the properties of PHBH become similar to those of 3HB homopolymer, resulting in loss of flexibility and an excessively high film-forming processing temperature, which is undesirable. If the composition of 3HH exceeds 25 mol%, the crystallization rate becomes too slow to be suitable for film-forming processing, and the degree of crystallization decreases, making the resin flexible and tending to decrease the flexural modulus. The composition ratio of PHBH can be measured by a known method, for example, NMR analysis. Microbial PHBH is a random copolymer. To adjust the molar ratio of the copolymer, there are several methods, such as selecting the bacterial cells, selecting the carbon source as the raw material, blending with PHBH of different molar ratios, and blending with 3HB homopolymer.

[0024] In one embodiment of the present invention, the mass average molecular weight of PHBH is preferably 50,000 to 700,000, more preferably 100,000 to 600,000, and even more preferably 200,000 to 400,000. When the mass average molecular weight of PHBH is within the above range, a film with excellent mechanical properties can be obtained. The mass average molecular weight of PHBH can be determined as a molecular weight converted into polystyrene by gel permeation chromatography (GPC, such as "Shodex GPC-101" manufactured by Showa Denko K.K.) using polystyrene gel (such as "Shodex K-804" manufactured by Showa Denko K.K.) in a column and chloroform as a mobile phase. As a measurement sample, a powder obtained by centrifuging an aqueous dispersion containing PHBH and then drying it is used. In the present invention, two or more types of PHBH having different composition ratios, mass average molecular weights, etc. may be mixed and used.

[0025] The weight ratio (solid content) of EVA to PHBH in the anchor layer is not particularly limited as long as the effects of the present invention are achieved, but is preferably 20:80 to 70:30, more preferably 25:75 to 60:40, and even more preferably 30:70 to 50:50.

[0026] In the present invention, the average particle size of PHBH in the coating material for forming the anchor layer is preferably 0.1 to 50 μm, more preferably 0.5 to 10 μm, and even more preferably 1 to 5 μm, from the viewpoint of blocking resistance. PHBH having an average particle size of less than 0.1 μm is difficult to achieve by microbial production, and even when obtained by chemical synthesis, a microparticulation operation is required. If the average particle size exceeds 50 μm, coating unevenness may occur. The average particle size of PHBH refers to the particle size corresponding to 50% accumulation of all particles in a normal distribution, measured by adjusting an aqueous suspension of PHBH to a predetermined concentration using a general-purpose particle sizer such as a Microtrac particle sizer (manufactured by Nikkiso Co., Ltd., FRA).

[0027] The anchor layer may contain, in addition to EVA and PHBH, other water-soluble resins and water-dispersible resins, and may further contain, as necessary, various auxiliaries that are blended into coating solutions in the papermaking field, such as dispersants, viscosity improvers, water retention agents, defoamers, water resistance agents, pH adjusters, cationic resins, anionic resins, UV absorbers, metal salts, lubricants, coloring dyes, pigments, etc. However, the anchor layer is preferably composed mainly of EVA and PHBH, and the ratio of the total amount of EVA and PHBH to the entire anchor layer (solid content) is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more.

[0028] The anchor layer can be formed by a known coating method. The coating amount (dry mass) of the anchor layer is not particularly limited as long as it can exhibit its performance. For example, it is 0.1 g / m per side. 2 More than 10.0g / m 2 Less than or equal to 0.5 g / m 2 More than 8g / m 2 Less than 1 g / m is preferable. 2 More than 5g / m 2 The following is even more preferred:

[0029] "Laminated paper" The laminate paper of the present invention has a laminate layer on the anchor layer of the laminate base paper described above. The method for forming the laminate layer is not particularly limited, and the laminate layer can be formed by a known method such as extrusion lamination or dry lamination. The material forming the laminate layer is not particularly limited, and known materials can be used. In the case of dry lamination in which a resin film is bonded, the resin film can be a film containing a material other than resin, such as an aluminum deposition film, an inorganic oxide deposition film, or a laminate film in which a metal foil such as aluminum foil and a resin film are laminated. In addition, the laminate layer can contain a lubricant, an inorganic filler, a plasticizer, an antiblocking agent, an odor absorber, a fragrance, an antioxidant, an antioxidant, a weather resistance improver, an ultraviolet absorber, a crystal nucleating agent, a release agent, a water repellent, an antibacterial agent, a sliding property improver, a colorant such as a pigment or a dye, etc.

[0030] By making the laminate layer mainly of a biodegradable resin such as the above-mentioned PHBH, polylactic acid, polycaprolactone, polybutylene succinate, or polybutylene succinate adipate, it is possible to reduce the adverse effects if the laminate layer is discharged into the environment as waste. When the laminate layer mainly comprises a biodegradable resin, it is preferable that the aerobic ultimate biodegradability in an aqueous culture medium according to JIS K6950 (evaluation device OxiTOP-IDS, value after 7 days at a test temperature of 33°C) is 40% or more. In this specification, "mainly composed" means 50% by weight or more.

[0031] The laminated paper of the present invention can be used for various purposes because the laminate layer can impart various properties to it. The laminated paper of the present invention can be used, for example, as waterproof paper, greaseproof paper, waterproof and greaseproof paper, heat seal paper, cup base paper, paper container base paper, etc. EXAMPLES

[0032] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, parts and % are by mass, respectively, unless otherwise specified.

[0033] Paper base material: basis weight 220g / m 2 Cup base paper (product name: CUP-HD, manufactured by Nippon Paper Industries Co., Ltd.) EVA1: Sumika Chemtex Co., Ltd., Sumika Flex S-408HQE, Tg-30℃, ethylene:vinyl acetate=40:60 EVA2: Sumika Chemtex Co., Ltd., Sumika Flex S-410HQ, Tg-18℃, ethylene:vinyl acetate=30:70 EVA3: Sumika Chemtex Co., Ltd., Sumika Flex S-401HQ, Tg-18°C, ethylene:vinyl acetate=30:70 EVA4: Sumika Chemtex Co., Ltd., Sumika Flex S-400HQ, Tg 0°C, ethylene:vinyl acetate = 20:80 EVA5: Sumika Chemtex Co., Ltd., Sumika Flex S-355HQ, Tg 10°C, ethylene:vinyl acetate = 10:90 PHBH: Kaneka Corporation, mass average molecular weight 600,000, average particle size 2 μm

[0034] A 23% by weight aqueous dispersion of ethylene-vinyl acetate copolymer resin and PHBH in a weight ratio (solid content) of 50:50 was applied to one or both sides of the paper substrate by the bar blade method, and the substrate was dried at 105°C for 1 minute to form an anchor layer, thereby preparing a laminate base paper. In the case of double-sided coating, the coating amount was the same on both sides. On the anchor layer of the obtained laminate base paper, PHBH having a mass average molecular weight of 600,000 was laminated by melt extrusion to a film thickness of 30 μm to obtain a heat seal paper.

[0035] (Evaluation method) The obtained laminate base paper and heat seal paper were evaluated as follows, and the results are shown in Tables 1 to 3. Blocking properties Two square test pieces with sides of 40 mm were cut out from the obtained laminate base paper, and the anchor layers were placed in contact with each other (Fig. 1A) or with the anchor layer and the paper substrate (Fig. 1B). They were then subjected to a force of 50 N / cm under conditions of 40°C and 80% RH. 2 A load of 1000 g was applied and the sample was left stationary for 24 hours. After standing, the appearance when peeling off the laminate base paper and the condition after peeling were visually checked and evaluated according to the following criteria. [Evaluation Criteria] 5: It peels off naturally. 4: There is weak resistance but it peels off. 3: The surface becomes rough after peeling. 2: Material failure occurs over less than 50% of the surface. 1: Cannot be removed or more than 50% of the surface is damaged. ·Laminate layer adhesion Two square test pieces with sides of 40 mm were cut out from the obtained heat seal paper, and the heat seal layers were brought into contact with each other and pressed at a pressure of 130°C and 1.5 kgf / cm. 2 The heat seal was performed with pressure applied for 3.0 seconds. A cutter blade was used to make a horizontal cut 2 mm deep between the opposing heat seal layers at the end of the test piece, and the heat seal layer was manually peeled off from the cut. The force felt when peeling and the condition after peeling were visually confirmed and evaluated according to the following criteria. [Evaluation Criteria] 5: Material failure occurs (paper substrate is destroyed). 4: Partial material failure occurs (paper base material is destroyed). 3: There is a strong sense of resistance, but no breakage of the material occurs. 2: There is some resistance, but it can be peeled off easily. 1: It can be peeled off very easily without any resistance.

[0036] [Table 1]

[0037] [Table 2]

[0038] [Table 3]

[0039] The laminate base paper obtained in the examples, in which the anchor layer contained EVA and PHBH, had excellent blocking resistance, whereas the laminate base paper obtained in the comparative examples, in which the anchor layer was made only of EVA, had poor blocking resistance. The laminate base paper obtained in the comparative example, in which the anchor layer was only EVA, had excellent adhesion to the laminate layer. According to the examples 1 to 5 and the comparative examples 1 to 5, when the anchor layer contained PHBH, the adhesion to the laminate layer tended to decrease, but in the example 5, in which EVA with a high molar ratio of vinyl acetate was used, the adhesion to the laminate layer did not decrease.

Claims

1. A laminate base paper comprising a paper substrate and, on at least one surface of the paper substrate, an anchor layer which is a coating layer containing an ethylene-vinyl acetate copolymer resin and PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)).

2. 2. The laminate base paper according to claim 1, wherein a weight ratio of the ethylene-vinyl acetate copolymer resin to the PHBH is 30:70 to 70:

30.

3. 3. A laminated paper comprising a laminate layer on the anchor layer of the laminate base paper according to claim 1 or 2.

Citation Information

Patent Citations

  • Biodegradable heat insulating container

    JP2018162075A

  • Cellophane laminate

    JP2024039713A

  • heat seal paper

    JP7285387B1

  • Laminate and use thereof

    WO2021100733A1

  • Material for paper containers for liquid, paper container for liquid, paper container for liquid for aseptic filling, and method for producing recycled pulp

    WO2021182183A1